Transdisciplinary education for sustainability. Creativity and awareness in teacher training - Echegoyen-Sanz, Yolanda; Morote, Álvaro; Martín-Ezpeleta, Antonio (Frontiers in Education, 2024)
Teacher training is a strategic aspect to achieve quality education and, therefore, bring closer Horizon 2030 and sustainability. The aim of this work is to present the outcome of an innovative transdisciplinary educational proposal with 176 primary teachers in training with the goal of raising their sustainability awareness. It was implemented at the same time in a Social sciences subject and in an Social sciences one demonstrating both its transdisciplinary nature and the fact that sustainability is a transversal aspect in the curriculum. A mixed methods research design was used. Work products were analyzed, such as the creation of a digital story for children about sustainability and some related activities. In addition, the perceived impact of the educational experience in the teaching-learning process and sustainability attitudes were assessed using two validated questionnaires. The results show a high level of perception of the impact of the experience in the motivation of preservice teachers, the learning of concepts related to the subject, and, especially, the usefulness of this proposal for their professional future. Furthermore, their sustainability attitudes at the end of the semester were very high, with scores above 4 (out of 5) for all measured dimensions. The relevance of advocating for a transdisciplinary education for sustainability, which begins in teacher training faculties, is concluded.